2003
DOI: 10.1182/blood-2002-07-2206
|View full text |Cite
|
Sign up to set email alerts
|

CD2 engagement induces dendritic cell activation: implications for immune surveillance and T-cell activation

Abstract: We have shown previously that primary dendritic cells and monocytes express equal levels of CD14 but are distinguishable by the presence of CD2 on dendritic cells. CD2 is known to mediate the activation of T and natural killer (NK) cells through its interaction with CD58. CD2 epitopes recognized by anti-T111, -T112, and -T113 monoclonal antibodies (mAbs) are present on dendritic cells. Here we show that CD2 engagement significantly increases class II, costimulatory (CD40, CD80, CD86), adhesion (CD54, CD58), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The post-GM-CSF data confirmed differentiation of hematopoietic elements into both myeloid (CD15, CD36) and lymphoid-like (CD2) lineages. 13,14 We also show HLA-DR, a major histocompatibility complex (MHC) class II marker for antigen-presenting cells, to be expressed in vivo as has been noted in vitro for hematopoietic progeny derived from hESCs. 15 MHC II molecules are decreased on most erythroid and myeloid differentiated cells.…”
Section: Resultsmentioning
confidence: 99%
“…The post-GM-CSF data confirmed differentiation of hematopoietic elements into both myeloid (CD15, CD36) and lymphoid-like (CD2) lineages. 13,14 We also show HLA-DR, a major histocompatibility complex (MHC) class II marker for antigen-presenting cells, to be expressed in vivo as has been noted in vitro for hematopoietic progeny derived from hESCs. 15 MHC II molecules are decreased on most erythroid and myeloid differentiated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Standard unstained, isotypestained, and positively stained control T cells were used for quadrant gate settings. Where indicated, results are expressed as an expression index (EI) (percentage positive population multiplied by the mean fluorescence intensity (MFI)) (40,41). RT-PCR and immunoblot analysis for MUC1 and ␤-actin expression were performed as described (18).…”
Section: Assessment Of Muc1 Expressionmentioning
confidence: 99%
“…In addition, several studies reported an increased number of circulating CD14 + CD16 + in the course of infections, inflammation, and malignant diseases (17)(18)(19)(20). Another subpopulation of circulating monocytes expresses the CD2 marker and these cells have been described as dendritic cells (21,22). In particular, we have recently reported that peripheral blood monocytes may differentiate into highly active antigen-presenting cells and CD14 + CD2 + monocytes can rapidly acquire the expression of the dendritic cell maturation marker CD83 after a short time (i.e., 4 hours) of incubation in the presence of IFN-a and granulocyte macrophage colony-stimulating factor (GM-CSF; ref.…”
Section: Introductionmentioning
confidence: 99%